About Comunes: challenges of the social movements ecosystem About Comunes: desafíos del ecosistema de movimientos sociales - Bastien Guerry; Samer Hassan; Pablo Rivière-Marichalar; Otros miembros del Colectivo Comunes.org (Revista Teknokultura, 2013)
The social movements suffer multiple difficulties in their organization, communication, collaboration and long-term planning. Comunes is a non-profit collective that aims to minimize these difficulties and to facilitate the work of social movements, through free/libre web-tools and resources that attempt to foster the commons. Los movimientos sociales sufren múltiples dificultades en su organización, comunicación, colaboración y planificación a largo plazo. Comunes es un colectivo sin ánimo de lucro con el objetivo de minimizar dichas dificultades y facilitar el trabajo de los movimientos sociales, mediante recursos y herramientas web libres, que tratan de fomentar los bienes comunes.